PENGEMBANGAN MULTIMEDIA PEMBELAJARAN BAHASA INGGRIS UNTUK SISWA KELAS X MENGENAI TEKS NEWS ITEM - Subadi, Subadi; Saharudin, Saharudin; Asyhar, Rayandra (Tekno - Pedagogi : Jurnal Teknologi Pendidikan, 2015)
This article is based on the development research that aims to develop multimedia of learning English which is attractive and effective for grade X Students about news item text. The development of the multimedia for learning English uses Lee and Owens model. The procedure of developing the multimedia covers four steps. They are: 1) need analysis and assessment, 2) designing multimedia learning, 3) developing and implementing the multimedia, and 4) evaluating the multimedia. The data of this research are compiled any sources i.e. validation result of leaning design expert, subject matter expert and learning media expert. It is also from students as treatment subjects and English lesson teacher. The treatment subjects are 39 students consisting of 3 students for personal treatment, 5 students for small group treatment and 31 students for field treatment. The results of the research show that: 1) developing the Macromedia Flash based multimedia of English learning for Class X was assessed by validators as learning media which is in good category and it is suitable to use. 2) the treatment subjects, students and English teacher gave response and conclusion that the multimedia is attractive for learning English, shown from the result of personal treatment subjects’ questionnaire of 88.7%, the result of small group treatment subjects’ questionnaire of 64.4% and the result of field treatment subjects’ questionnaire of 84.2%, therefore, the average of total treatment subjects’ questionnaire is 79.7%, then 3) this multimedia can be used effectively to achieve learning competencies, proven by the result of increasing score gained by the students in pre-test and post-test which is 72.03%. Keyword: development research, multimedia of learning English, news item text